PROYEKSI INDONESIA BERGABUNG DALAM TRANS-PACIFIC PARTNERSHIP - Arthuur Jeverson Maya (Kajian Asia Pasifik, 2017)
This article discusses the projection high standard free trade cooperation of the Trans-Pacific Partnership (TPP) which attracts Indonesia to join under President Joko Widodo (Jokowi). It is analyzed predictively calculation of the situation that occurred if Indonesia was determined to join TPP in the future. This is analyzed using the concept of political communication, the concept of neoliberalism, and the critical theory of neomarxism, supported by qualitative research methods and data collection from secondary sources. Found evidence indicating the inability of Indonesia's competitiveness against majority member states of TPP. As a result, they have the potential to engage in exploitative, dependent, and monopoly relationships with Indonesia's economic and social if join TPP at this time. Therefore, it is recommended to reject TPP until Indonesia has the optimal competitiveness ability to refer to the effectiveness, efficiency, and productivity of the population, low poverty, high gross national income percapita, high value human development index, high value global competitive advantage, anti-corruption business bureaucracy, and adequate infrastructure. Keywords: Trans-Pacific Partnership (TPP), Indonesia, Neoliberalism, Neomarxism Abstrak Artikel ini membahas proyeksi kerja sama perdagangan bebas berstandar tinggi Trans-Pacific Partnership (TPP) yang menarik minat Indonesia dibawah kepemimpinan Presiden Joko Widodo (Jokowi) untuk bergabung di dalamnya. Ia dianalisis prediktif mengenai kalkulasi situasi yang terjadi apabila Indonesia nekat bergabung dalam TPP di masa depan. Ini dianalisa menggunakan konsep komunikasi politik, konsep neo-liberalisme, dan teori kritis neo-marxisme, didukung metode penelitian kualitatif dan pengumpulan data dari sumber sekunder. Ditemukan bukti-bukti yang mengindikasikan ketidakmampuan Indonesia bersaing dengan mayoritas negara-negara anggota TPP. Akibatnya, mereka berpotensi melakukan hubungan eksploitatif, ketergantungan, dan monopoli ekonomi dan sosial indonesia jika memutuskan bergabung dalam TPP saat ini. Oleh sebab itu, direkomendasikan untuk menolak TPP sampai Indonesia memiliki kemampuan daya saing optimal mengacu efektivitas, efisiensi, dan produktifitas populasi, kemiskinan rendah, pendapatan nasional perkapita tinggi, indeks pembangunan manusia tinggi, keunggulan nilai dalam menghadapi persaingan global, birokrasi bisnis anti-korupsi, dan infrastruktur yang memadai. Kata Kunci: Trans-Pacific Partnership (TPP), Indonesia, Neoliberalisme, Neomarxisme